The Influence of Caregivers' Communication Styles on the Development of Discipline in Foster Children in Orphanages - Illahi, Astri Hidayah; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research was motivated by the fact that some foster children in orphanages still have not developed a disciplined character. This research aims to analyze various communication styles of caregivers that can support the development of a disciplined character in foster children in orphanages. The method used is a literature study which is carried out through library data collection, reading, and note-taking, as well as managing research materials. The problems discussed in this research are motivated by the character of foster children. The main character discussed is a disciplined character because the importance of a disciplined character reflects how foster children carry out the rules in orphanages. The findings from this study suggest that; (1) several phenomena of undisciplined character in foster children in orphanages include lazy attitudes of children, the presence of disobedient children, lack of self-awareness in implementing disciplinary attitudes such as not obeying applicable regulations. (2) several communication styles that can be applied by caregivers include a passive communication style, an aggressive communication style, a passive-aggressive communication style, and an assertive communication style which is considered the most effective communication style. Based on the findings of this study, it is hoped that those who provide care will consider how they communicate, as this has an impact on children in foster care.